(untitled) (Journal of the College of Basic Education, 2022)
The condition is one of the topics based on the occurrence of a thing due to the occurrence of another, and it is one of the grammatical and rhetorical topics that depend in its basis on a set of tools, including names and letters, many of which occurred in the book Al-Kafi by al-Kulayni, and it is a book that includes the sayings of the Prophet Muhammad and his pure family  as they were represented in their speech by various conditional topics Her tools.